Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Finding $$\int \frac{1}{x}\sqrt{1+\frac{1}{x^4}}\,dx$$


I suppose I need integration by parts and trigo substitution

Let $u=\frac{1}{x} \Rightarrow du = -\frac{1}{x^2} dx$

Let $dv = \sqrt{1+(\frac{1}{x^2})^2}$, $\frac{1}{x^2} = \tan{\theta}$. Is my substitution OK?

So $x=\frac{1}{\sqrt{\tan{\theta}}} \Rightarrow dx = -\frac{\sec^2{\theta}}{2\sqrt{\tan{\theta}}}\,d\theta$. But this will be very complicated to integrate later?

Am I supposed to be trying something else?


UPDATE: An attempt

$$\int \frac{1}{x} \sqrt{1+\frac{1}{x^4}} dx$$

Let $u = \frac{1}{x} \Rightarrow du = -\frac{1}{x^2} dx$

Let $dv = \sqrt{1+(\frac{1}{x^2})^2} dx$

Let $\alpha = \frac{1}{x^2} \Rightarrow d\alpha = -\frac{1}{2x^3}$

$dv=\sqrt{1+\alpha^2} d\alpha$

Let $\alpha = \tan{\theta} \Rightarrow d\alpha = \sec^2{\theta} d\theta$

$dv = \sqrt{1+\tan^2{\theta}} \sec^2{\theta} d\theta = \sec^3{\theta}$. Looks wrong here ?

share|improve this question
2  
try $u=\frac{1}{x^2}\Rightarrow du = \frac{-1}{2x^3}$. This will lead to $-\frac{1}{2}\int u^2\sqrt{1+u^2}\,du$ which can be solved by substituting a hyperbolic function –  example Apr 11 '12 at 11:18
    
substitute : $u=\frac{1}{x^4}$ –  pedja Apr 11 '12 at 11:28
    
Sry, made a small mistake in my head while writing that comment. See my solution below. –  example Apr 11 '12 at 11:33
add comment

2 Answers 2

up vote 5 down vote accepted

$$I = \int \frac{\sqrt{x^4+1}}{x^3} \mathrm{d}x$$

Substitute $u=\sqrt{x^4+1}, \mathrm{d}u=\frac{2x^3}{\sqrt{x^4+1}}\mathrm{d}x$

$$\int \frac{u^2}{2(u^2-1)^{\frac{3}{2}}} \mathrm{d}u$$

Now substitute $u=\sec \theta$ $\mathrm{du} = \sec \theta \tan \theta \mathrm{d}\theta$

Then $(u^2-1)^{\frac{3}{2}} = \tan^3 \theta$

$$I = \frac{1}{2}\int \csc^2 \theta \sec \theta \mathrm{d}\theta = \frac{1}{2}\int (\cot^2 \theta+1) \sec \theta \mathrm{d}\theta$$

And take it from there

share|improve this answer
add comment

Usually we want to get rid of the square root. One way to do so is to bring in into the form $\sqrt{1+\cosh^2(u)}$ so lets try this in two steps $$\frac{1}{x^2}=v \Rightarrow dv = \frac{-1}{2x^3}dx \Leftrightarrow dx = -2x^3 \, dv$$ $$ \int \frac{1}{x}\sqrt{1+\frac{1}{x^4}}\,dx = \int \frac{-2x^3}{x}\sqrt{1+v^2}\,dv = -2\int \frac{1}{v}\sqrt{1+v^2}\,dv$$

With $v=\cosh(u) \Rightarrow dv = \sinh(u)\,du$ and $1+\cosh^2(u) = \sinh^2(u)$ follows $$ ... = -2\int\frac{\sinh^2(u)}{\cosh(u)} \,du$$

This will become a bit messy from here on. Seeing how the final result is ... $$ -\frac{1}{2} \sqrt{1+\frac{1}{x^4}}+\frac{1}{2}\sinh^{-1}\left(x^2\right) $$

share|improve this answer
    
Is $\cosh$ the same as $\arccos$ or $\cos^{-1}$? Also I think $$\int \frac{1}{x}\sqrt{1+\frac{1}{x^4}}\,dx = -2\int \color{red}{\frac{1}{v}}\sqrt{1+v^2}\,dv$$, is wrong? Should it be $\frac{1}{\sqrt{v}}$ –  Jiew Meng Apr 11 '12 at 11:39
1  
@Jiew it is the hyperbolic cosine. en.wikipedia.org/wiki/Hyperbolic_functions . Here we only use $\frac{d}{dx}\cosh(x)=\sinh(x)$, $\frac{d}{dx}\sinh(x)=\cosh(x)$ and $\sinh^2(x)-\cosh^2(x)=1$ though. –  example Apr 11 '12 at 11:41
    
@Jiew: added 2 more steps in the equations to show that it indeed is $\int\frac{1}{v}...dv$ –  example Apr 11 '12 at 11:43
    
@Jiwe: ahhh, but I made a mistake. Should be $\sinh^2(u) / \cosh(u)$. Let me see whether I can correct that. –  example Apr 11 '12 at 11:46
    
Hmm don't see a nice way to do the last steps. Maybe someone can fill them in? –  example Apr 11 '12 at 11:55
show 1 more comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.